Wisdom: The Missing Dimension in Information and Communication Technology (ICT) (American Journal of Islam and Society, 2003)
The levels of knowledge hierarchy (i.e., data, information, knowledge, and wisdom), are described in the Qur’an, the ahadith, and the literature produced during Islamic civilization’s Golden Age. They also have been discussed by western and non-Muslim scholars. However, while implementing and using information and communication technology (ICT), only the first three levels are currently being explored and utilized. Wisdom has not been discussed to any great extent. ICT has designed systems to assist us and has improved our life and work. However, such tools as decision-support systems and executive information systems comprise only data, information, and knowledge. Comprehensiveness does not guarantee the possession of wisdom. Taking things apart is knowledge; putting things together is wisdom. Muslim scholars of the Golden Age analyzed data, drew relationships and interpreted data to create information, identified and determined the pattern to represent knowledge, and understood the foundational principles for the patterns to implement wisdom. Wisdom must be included if ICT is to be complete. People, organizations, and the nation must strive for wisdom as the ultimate goal: from an information society to a knowledge society to a wisdom society, and from information workers to knowledge workers to wisdom workers.